Improved Magnetic and Ku-Band Microwave Response in Ba0.85la0.15fe12-Xcoxo19 Hexaferrites - Casagrande-Denardin, J (Elsevier Ltd, 2025)
Lanthanum and cobalt substituted barium hexaferrite, Ba0.85La0.15Fe12-xCoxO19, was prepared by the solid-state ceramic method. The effect of heterovalent substitution on the improved magnetic and Ku band (12.4–18 GHz) microwave performance was studied. X-ray diffraction, Fourier transform infrared and Raman spectroscopy confirmed the presence of magnetoplumbite phase and effective substitution of heterovalent ions in the crystal system. Microstructural analysis revealed highly dense, well developed hexagonal grains for substituted samples. Magnetic measurements showed an increase in magnetic saturation from 58 to 62 emu/g and coercivity from 1.3 to 1.9 kOe with La-Co substitution, while anisotropy, calculated from the law of approaching saturation, exhibited a gradual decrease. Dielectric permittivity and permeability were improved with La-Co substitution, leading to enhanced impedance matching in the absorber at the Ku-band frequency range. Microwave absorption studies revealed a broad effective absorption bandwidth (EAB) exceeding 1 GHz for substituted samples. The maximum EAB of 3.01 GHz was observed for Ba0.85La0.15Fe11.9Co0.1O19 sample with a 1.4 mm thickness, while the reflection loss minimum of −21.88 dB (absorption >99.9 %) was noted for 1.6 mm at 13.30 GHz. The observed results were promising for the microwave devices in Ku band frequency. © 2025 Elsevier Ltd and Techna Group S.r.l.